Shorter myotomy on the gastric site (≤2.5 cm) provides adequate relief of dysphagia in achalasia patients. Issue 5 (24th April 2014) - Salvador, R.; Caruso, V.; Costantini, M.; Parise, P.; Nicoletti, L.; Cavallin, F.; Zanatta, L.; Bardini, R.; Ancona, E.; Zaninotto, G.
Summary The right length of the myotomy on the gastric side for esophageal achalasia is still a debated issue. We aimed to investigate the final outcome after classic myotomy (CM) as compared with a longer myotomy on the gastric side (LM) in two cohorts of achalasia patients. Forty‐four achalasia patients who underwent laparoscopic Heller–Dor were considered; patients with a sigmoid‐shaped esophagus were excluded. Symptoms were scored using a detailed questionnaire for dysphagia, regurgitation, and chest pain. Barium swallow, endoscopy, and esophageal manometry were performed before and 6 months after the surgical treatment; 24‐hour pH‐monitoring was also performed 6 months after the procedure. CM was defined as a gastric myotomy length in the range of 1.5–2.0 cm, while LM was 2.5–3 cm in length. The surgical treatment (CM or LM) was adopted in two consecutive cohorts. Treatment failure was defined as a postoperative symptom score >10th percentile of the preoperative score (i.e. >8). Of the 44 patients representing the study population, 20 had CM and 24 had LM. The patients' demographic and clinical parameters (age, sex, symptom score, duration of symptoms, esophageal diameter, and manometric pattern) were similar in the two groups. The median follow up was 24 months (interquartile range 12–39). One patient in each group was classified as a treatment failure. After the treatment, there was a significant decrease in both groups' symptom score, and resting and residual pressure (P < 0.01), with no statistically significant differences between the two groups in terms of postoperative symptom score, resting and residual pressure, or total and abdominal lower esophageal sphincter length and esophageal diameter. Extending the length of the myotomy on the gastric side does not seem to change the final outcome of the laparoscopic Heller–Dor procedure.